Efek Seduhan Kopi Robusta terhadap Jumlah Limfosit pada Daerah Tarikan Ligamen Periodontal Gigi Marmut (Cavia Cobaya) yang Diinduksi Gaya Mekanis Ortodonti - Ginanjar Hidayatullah; Herniyati Herniyati; Leliana Sandra Deviade Putri (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Malocclusion is an occlusion that deviates from the normal state, so it needs to be treated using an orthodontic device. The formation of new alveolar bone after obtaining an orthodontic force will be surrounded by osteoid bones are not stable enough (relapse). Robusta coffee (Coffea robusta) has flavonoids which can increase lymphocyte proliferation. The purpose of this study was to analyze the effect of robusta coffee on the number of lymphocyte cells in the tension area of marmot’s (Cavia cobaya) periodontal ligament which induced by mechanical orthodontic forces. This type of research is laboratory experimental with the Post Test Only Control Group Design. The average number of lymphocyte cells in group A = 0.75, B = 1.45, C = 1.26, D = 1.54. One-way Anova test results showed that the number of lymphocyte cells in all groups showed a significant difference (p <0.05). The results of the post hoc LSD test showed that group A had significant differences with group B and group D (p <0.05). While group C did not have a significant difference with group A (p> 0.05). The conclusion obtained is that the provision of robusta coffee brew for 2 weeks can increase the number of lymphocyte cells in the tension area of marmot’s (Cavia cobaya) periodontal ligament which induced by orthodontic mechanical forces compared to without robusta coffee brew.